Impacts of climate change on agricultural production in Nepal: Case of Kavre and Jumla districts (Nepal Journal of Environmental Science, 2014)
The study the analyzed relationship of climate change with agricultural production in Kavre and Jumla districts. The specific objective of the study was to find out the dimension and linkage between agricultural production and climatic parameters in Kavre and Jumla. Time series data were analysed for the study. The data was sourced from the Department of Hydrology Meteorology, Department of Agriculture, and National Bureau of Statistics. Descriptive statistics, linear analysis test and back ward difference filter were the analytical tools used to determine the impact of climate change on productivity. During harvest period, the correlation of rice yield with temperature and rainfall was negative at Kavre but positive at Jumla. Similarly, the correlation of wheat yield with temperature and rainfall was positive at Kavre but negative at Jumla. The result showed that extreme fluctuation in weather caused negative impact on production in Jumla in compared to Kavre districts.